Tradition of Nyadran: As A Material for the Development of the Teaching Material of Social Sciences Education in the Secondary School - Wibowo, Guntur Arie; Karim, Aim Abdul; Hasan, Said Hamid; Ruhimat, Mamat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to provide an overview of the existing Nyadran tradition literature as material for social studies development in junior high schools. In addition, it is also intended to create a conceptual model related to the use of the Nyadran tradition. This article is a conceptual article that covers the basics, basic competencies, and curriculum. This research is qualitative research with case study methods. The data collection technique is derived from interviews with the main data source of the Klumutan village community, while the other data is from the documentation of the profile of the Klumutan town and the photographs of the implementation of traditional Clumutan. Sampling techniques using purposive sampling. Data validity testing using source triangulation and methods Analysis techniques using interactive data analysis models: data collection, data reduction, data presentation, and conclusion drawings. The results of this research consist of three conclusions. First, the Nyadran tradition can be used as a source of social studies development in junior high schools. This is because this tradition contains moral teachings and local wisdom relevant to the vision of social science, namely civics education. Moreover, the oral tradition, which is part of anthropology and history, has the same characteristics as social studies material, which combines social science disciplines. The two high social values of the Nyadran tradition can be used as a source of social science learning. These values mean moral, social, cultural, spiritual, and environmental. Third, the development of oral traditions as teaching materials can be carried out through three stages, namely: (a) the analysis stage (defining the oral traditions and their relevance to the curriculum); (b) the design and development stage (determining the form and structure of the learning materials needed); and (c) implementation stage.